HUBUNGAN KARAKTERISTIK PEMBIMBING KLINIK DENGAN PENCAPAIAN KOMPETENSI KLINIK MAHASISWA PROFESI NERS - Padaunan, Ellen; Sigar, Dira M. E. (Klabat Journal of Nursing, 2025)
Nursing professional students are required to master theoretical knowledge and possess competent practical skills in providing patient care during clinical practice. Clinical instructors play an important role in supporting the achievement of nursing student’s clinical competence, especially when they possess positive instructor characteristics. The aim of this study was to determine the relationship between clinical instructor characteristics and the clinical competence of nursing professional student at the Faculty of Nursing, Klabat University. The design of this study was quantitative research using descriptive research methods with a cross-sectional approach. The sample consisted of 96 respondents. Statistical test results showed that the description of clinical supervisors was in the high category, with 37 (38.6%) respondents. The description of clinical competence was mostly in the moderate category, with a frequency of 38 (39.7%). The results of the study show a correlation between the characteristics of clinical supervisors and the achievement of clinical competence of nursing students at Unklab with a p-value of 0.022 (<0.05) and a correlation coefficient of (r) = 0.234, which means that there is a significant relationship between the characteristics of clinical supervisors and the achievement of clinical competence of nursing students and has a weak positive relationship. Recommendations for further research include investigating other factors that may influence the achievement of nursing students' competencies, such as anxiety levels, practice environment, educational institution support, interests, and attitudes. Mahasiswa profesi ners dituntut menguasai pengetahuan dan memiliki kemampuan praktik yang kompeten dalam merawat pasien didunia praktik lapangan dan pembimbing klinik merupakan seorang yang memiliki peran penting dalam pencapaian mahasiswa profesi ners jika memiliki karakteristik pembimbing yang baik. Tujuan dari penelitian ini untuk mengetahui hubungan karakteristik pembimbing klinik dengan pencapaian kompetensi klinik mahasiswa profesi ners fakultas keperawatan Unklab. Desain penelitian ini adalah penelitian kuantitatif dengan metode penelitian deskriptif dengan pendekatan penelitian cross sectional. Sampel yang digunakan sebanyak 96 responden. Hasil uji statistik menyatakan bahwa gambaran pembimbing klinik berada pada kategori tinggi sebanyak 37 (38,6%). Untuk gambaran kompetensi klinik mayoritas berada pada kategori sedang dengan frekuensi 38 (39,7%). Hasil penelitian ada korelasi antara karakteristik pembimbing klinik dengan pencapaian kompetensi klinik mahasiswa profesi ners Unklab dengan nilai p-value = 0,022 (<0,05) dengan nilai koefisien korelasi (r) = 0,234 yang artinya ada hubungan yang signifikan antara karakteristik pembimbing klinik dengan pencapaian komptenesi klinik mahasiswa profesi ners dan memiliki hubungan yang lemah kearah yang positif. Rekomendasi untuk penelitian selanjutnya agar meneliti lebih lebih lanjut mengenai faktor -faktor lain yang dapat mempengaruhi pencapaian kompetensi mahasiswa profesi ners seperti tingkat kecemasan, lingkungan praktek, dukungan institusi pendidikan, minat dan sikap.